2017
DOI: 10.21767/2572-5610.10027
|View full text |Cite
|
Sign up to set email alerts
|

Differentiating Multiple Sclerosis from Myalgic Encephalomyelitis and Chronic Fatigue Syndrome

Abstract: Multiple Sclerosis (MS), Myalgic Encephalomyelitis (ME), and Chronic Fatigue syndrome are debilitating chronic illnesses, with some overlapping symptoms. However, few studies have compared and contrasted symptom and disability profiles for these illnesses for the purpose of further differentiating them. The current study was an online self-report survey that compared symptoms from a sample of individuals with MS (N = 120) with a sample of individuals with ME or CFS (N = 269). Respondents completed the self-rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 25 publications
2
13
0
Order By: Relevance
“…In our study, we did not observe such a phenomenon, nor did we determine the optimum level of activity. Interestingly, Janson et al compared ME/CFS with MS and reported significantly more functional limitation and more severe symptoms in ME/CSF patients than those with MS [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, we did not observe such a phenomenon, nor did we determine the optimum level of activity. Interestingly, Janson et al compared ME/CFS with MS and reported significantly more functional limitation and more severe symptoms in ME/CSF patients than those with MS [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chronic Illness sample. The Chronic Illness respondents were from a convenience sample of adults living with chronic illnesses, including ME/CFS, collected by investigators at DePaul University [26]. Participants were recruited online using support groups, research forums, and social media platforms.…”
Section: Participantsmentioning
confidence: 99%
“…In a qualitative study of people living with both multiple sclerosis (MS) and late-stage kidney disease, limitation of activities was mentioned by multiple participants as a driving factor in their suicidal ideation [26]. This finding has particularly salient implications for ME/CFS, which has been suggested in multiple studies to reduce function even more than MS [27,28]. Thus, one might expect to see an even greater risk of suicide in ME/CFS than in other chronic illnesses with less impaired functionality.…”
Section: Risk Factors For Suicidementioning
confidence: 99%